Ratification and Consequences of Sexual Offenses in the Criminal Code of Georgia - Mailashvili, Jumber (Journal of Legal Studies, 2021)
This paper will discuss the issues of qualification of crimes against Sexual Freedom and Inviolability considered by Chapter 22 of Criminal Code of Georgia, which were made in the Criminal Code of Georgia after the Parliament of Georgia ratified the Council of Europe Convention on “preventing and combating violence against women and domestic violence” (Istanbul Convention) adopted on May 11, 2011. Georgia signed this Convention on June 19, 2014. This paper will discuss the relative aspects of qualifying circumstances and disposition of rape and other related corpora delicti and their understanding in a new manner. The article will study the pros and cons that resulted in the fundamental changes made to the Criminal Code of Georgia on May 30, 2018, after the ratification of the "Istanbul Convention". The concept prevailing, in theory, provides a new definition about what problems were solved and what contradictions arose from the new changes. In court practice, there still prevails the view that in order for the action to be assessed as rape, it is necessary for a woman to carry out “selfless” resistance to the offender. However, there are frequent cases when no signs of resistance are found on the victim’s body. Given the above, as evidence of the absence of consent is not often established to a high standard by the investigation (for example, in the event of a threat of violence), the case ends with the acquittal of the accused. The article will present recommendations on making changes in some components of the action by the Parliament of Georgia in the future. Based on the scientific literature and the legislation, both, main and additional qualifying elements considered by the disposition of the given Articles will be discussed in detail.